Application of Multi-pass Circulating Fluidized Bed in Integrated Energy Service - Feng HAN; Kunlin CONG; Qinghai LI; Yanguo ZHANG; Jiaoping YAN; Feng HU (发电技术)
Park level clean heating is an urgent problem to be solved in integrated energy service. The multi-pass circulating fluidized bed technology adopts a three-stage furnace structure to form a two-stage material circulation in the furnace, which solves the problem of miniaturization of traditional circulating fluidized bed boilers. The industrial practice has proved that the multi-pass circulating fluidized bed boiler can use biomass, industrial solid waste, coal and other fuels. The thermal efficiencies of various fuels reach 88%~92%, and the emissions of the pollutants meet the required permissible effluent concentrations of the national standards and local standards. The multi-pass circulating fluidized bed technology has the advantages of decentralized energy utilization and simultaneous application of multiple fuels, which can be effectively applied to park level integrated energy service.